Penerapan Metode Dempster Shafer Pada Sistem Pakar Diagnosa Penyakit Usus Halus - Nugroho, Fifto; Bani, Alexius Ulan (STMIK Budi Darma, 2022)
The small intestine is a food processing factory where nutrients are digested and absorbed completely when the small intestine is in good condition. However, many of us have an unhealthy small intestine, so the small intestine does not function properly. Health problems in the small intestine can occur from different factors such as the most dominant factor is food and drink, health awareness is still low, the habit of always wanting to live a practical life and lack of knowledge of healthy living and little knowledge about the problem of early symptoms of a disease. which is the main factor in treating the disease so that it becomes severe. If the patient is late in receiving information about his illness, the patient will be treated by the doctor too late. The doctor's knowledge can be implemented in an expert system system. The expert system method used to find diagnostic confidence uses the Dempster Shafer method. With the aim of making it easier for the public to find out what small intestine they suffer from and be able to check them early. Where the method of finding diagnostic confidence uses the Dempster Shafer method where the final result of this study produces an accurate diagnosis with a sample of symptom data used by 32% with Dianoses are less likely to suffer from Small Intestine Tract Blockage yang selalu ingin menjalani hidup secara praktis, serta cara berpikir yang cenderung mengarah pada kehidupan yang tidak sehat, dan gejala awal penyakit. merupakan bagian dari faktor. sakit.